1994
DOI: 10.1111/j.1600-079x.1994.tb00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of melatonin treatment on both locomotor activity and brain serotonin release in rats

Abstract: The effects of intraperitoneal administration of pharmacological doses of melatonin (60 mg/kg) on both locomotor activity and brain monoamine release were assessed in rats. The spontaneous levels of either horizontal motion, vertical motion, or total distance traveled were decreased following melatonin injection. On the other hand, the spontaneous levels of postural freezing increased after treatment. External heat exposure (36 degrees C) produced increases in locomotion (including horizontal motion, vertical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…In contrast to BZPs, 5-HT 2C receptor antagonists do not modulate 5-HT release in corticolimbic structures (Gobert et al 2000;Millan et al 2000b) and, accordingly, SB243,213 failed to modify extracellular levels of 5-HT in FCX or dorsal hippocampus. Though it has been proposed that high doses of melatonin modulate cerebral 5-HT release under certain conditions, data remain fragmentary (Chuang and Lin 1994;Yoshioka et al 2000) and no effect of melatonin on extracellular levels of 5-HT was observed herein. In line with this lack of influence of SB243,213 and melatonin on 5-HT levels, they were not affected by agomelatine.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast to BZPs, 5-HT 2C receptor antagonists do not modulate 5-HT release in corticolimbic structures (Gobert et al 2000;Millan et al 2000b) and, accordingly, SB243,213 failed to modify extracellular levels of 5-HT in FCX or dorsal hippocampus. Though it has been proposed that high doses of melatonin modulate cerebral 5-HT release under certain conditions, data remain fragmentary (Chuang and Lin 1994;Yoshioka et al 2000) and no effect of melatonin on extracellular levels of 5-HT was observed herein. In line with this lack of influence of SB243,213 and melatonin on 5-HT levels, they were not affected by agomelatine.…”
Section: Discussioncontrasting
confidence: 55%
“…30 mg kg −1 , p.o.) of melatonin may modulate (enhance or reduce) 5-HT release within some cerebral structures (Chuang and Lin 1994;Yoshioka et al 2000), whereas other studies, also with high doses, led to the conclusion that melatonin does not affect 5-HT release in main projection areas of 5-HT neurones such as frontal cortex and hippocampus (Millan et al 2005). Using considerably lower doses, ex vivo studies indicated that melatonin (0.5 or 1 mg kg −1 , s.c.) increased tissue levels of 5-HT and 5-HIAA in most hypothalamic structures, in the amygdala and in the midbrain, but displayed an inhibitory effect on 5-HT turnover in suprachiasmatic nuclei (Miguez et al 1994(Miguez et al , 1996.…”
Section: Discussionmentioning
confidence: 95%
“…Melatonin has anticonvulsant and depressive effects (Acuna-Castroviejo et al, 1995) and anti-excitotoxic efficacy in reduction of induced locomotor responses (Chuang and Lin, 1994). Melatonin has a potent protective effect against neurological injuries produced by agents or processes such as aging (Reiter et al, 2001;Sharman et al, 2002), stroke , trauma (Mesenge et al, 1998;Pei et al, 2002), ischemia (Sun et al, 2002), and excitotoxins like KA and quinolinic acid (Melchiorri et al, 1995;Giusti et al, 1996;Tan et al, 1998;Chung et al, 2003).…”
Section: Neuroprotective Role Of Melatonin In Da-induced Neurotoxicitymentioning
confidence: 97%